HBR guide to critical thinking - Johnston, Karen Ruth; Pollock, Brandon (Harvard business review guides., 2023)
Tackle complex situations with critical thinking. You're facing a problem at work. There are many ways you can approach the situation, but each comes with its own pros and cons. How do you sort through all the information so that you know you're taking the right path? The answer is in how you think. The HBR Guide to Critical Thinking will help you navigate your most challenging issues, from difficult problems to tough decisions to complex scenarios. By carefully observing the situation, gathering information, inviting other perspectives, and analyzing what's in front of you, you can move forward with confidence while building this crucial leadership skill. You'll learn how to: question your assumptions; keep an open mind to opposing viewpoints; sidestep cognitive biases; use data-when appropriate; grow comfortable with ambiguity; and find innovative and creative solutions. Arm yourself with the advice you need to succeed on the job, with the most trusted brand in business. Packed with how-to essentials from leading experts, the HBR Guides provide smart answers to your most pressing work challenges.